Las we współczesnym reportażu radiowym (ucieczka przed "wspaniałym światem") - Klimczak, Kinga (Acta Universitatis Lodziensis. Folia Litteraria Polonica, 2009)
Where can we escape from commercialization of, where can we find true and live with unity with ourselves? Many people chose forest like a shelter from hypocrite. Forest became their home. About that people - in radio’s reportages - isolated from society, loved nature, animals and being with them, refers this paper.